The Influence of Skirt Depth and Compartments on the Load Response of Skirted Foundations in Sand - Tieh, Yousif Jawad; Ahmed, Mahmood D. (Engineering, Technology & Applied Science Research, 2025)
This experimental study examines how shallow foundations with skirted designs containing internal partitions react to vertical and inclined loads at 0°, 5°, 10°, and 15° angles in sandy soil with 30% relative density. The experimental setup included Linear Variable Differential Transformers (LVDTs) for the settlement measurements, load cells for the load application, and a data logger for precise data acquisition. The research used square foundation models (10 cm × 10 cm) with steel skirts, which were tested at three skirt depths (0.5B, 1B, and 1.5B) with three internal partition configurations: no partition, two compartments, and four compartments. The results demonstrate that both the bearing capacity and settlement performance are substantially enhanced when the skirt depth increases and the number of the internal partitions increases. Under vertical load, the Bearing Capacity Ratio (BCR) increased to 4.4 from 2.18 when the skirt depth reached 1.5B for unpartitioned skirts, while two-compartment skirts achieved 5.46 at a skirt depth of 1.5B and four-compartment skirts reached 7.09 at the same depth. The Settlement Reduction Factors (SRF) at 1.5B depth were 0.92 for the unpartitioned skirts, 0.946 for two-compartment skirts, and 0.968 for four-compartment skirts. The foundation's bearing capacity decreases when the load becomes inclined, yet, the skirted foundation maintains its performance advantage. At 15°, The BCR of the four-compartment skirt increased from 3.48 at 0.5B to 4.8 at 1B and reached 6.705 at 1.5B depth, while the SRF values were 0.84, 0.87, and 0.91 respectively. The research demonstrates that the skirted foundations with internal partitions deliver superior performance in sandy soils when subjected to vertical or inclined loading, thus making them suitable for engineering projects that require resistance to both the vertical and inclined load resistance.